Organic-inorganic hybrid perovskite – TiO2 nanorod arrays for efficient and stable photoelectrochemical hydrogen evolution from HI splitting. (June 2019) - Luo, J.; Yang, H.; Liu, Z.; Li, F.; Liu, S.; Ma, J.; Liu, B.
Abstract: Solar-driven photoelectrochemical (PEC) hydrogen production offers a promising solution to simultaneously tackle the global energy crisis and the environmental pollution. Herein, we report a PEC cell of organic-inorganic hybrid perovskite (methylammonium lead iodide, MAPbI3 )- TiO2 nanorod array (TNAs) for efficient and stable hydrogen evolution in aqueous hydrogen iodide (HI) solution. The built-in electric field created across the MAPbI3 -TiO2 junction is able to efficiently separate the electron-hole pairs photogenerated in MAPbI3 with electrons quickly injected from MAPbI3 to TiO2, which are then transported along the one-dimensional TiO2 nanorod channels to the counter electrode to reduce proton to evolve hydrogen. The optimized MAPbI3 -TNA PEC cell exhibits a high photocurrent density of 1.75 mA cm −2 at 0.14 V (vs. Ag/AgCl) under AM 1.5G illumination, which is able to stably produce molecular hydrogen at a rate of 33.3 μmol cm −2  h −1 for more than 8 h. Highlights: A PEC cell of MAPbI3 -TiO2 nanorod array (TNAs) for hydrogen evolution in aqueous iodide solution is reported. The built-in electric field created across the MAPbI3 -TNA junction can efficiently separate electron-hole pairs. The optimized MAPbI3 -TNA PEC cell exhibits a high photocurrent density and stability.